EVALUASI PERKERASAN LENTUR MENGGUNAKAN METODE PAVEMENT CONDITION INDEX (PCI) DAN SURFACE DISTRESS INDEX (SDI) BERDASARKAN DATA ALAT PROFILOMETER (STUDI KASUS: JALAN LINGKAR NAGREG JAWA BARAT) - DEWI ARIANI (NIM: 26913306), INDAH
Road is one of the land transportation infrastructure that plays an important role, therefore it needs to be well managed in order to have an optimal service level. The evaluation of pavement performance should be done to determine the right maintenance Program by first conducting road survey conditions. Profilometer is one of the modern surveying instrument which is often used nowadays. The output data of this instrument are various such as Geometry, Profilometry, Road Condition Video, and GPS. The Purposed of this Research is to analyze the pavement functional condition refer to Pavement Condition Index (PCI) and Bina Marga (Combination of International Roughness Index (IRI) and Surface Distress Index (SDI)) Method based on Profilometer’s Output Data. The Data later was processed with software. The result of the comparison on two method is from 54 (fifty four) segment units, there are 11 (eleven) segment units (±20%) which obtain different result of functional condition. As for the Bina Marga Method (combination of IRI and SDI) shows that IRI has important role for controlling the quality of data since it obtained from the tools while the value of SDI is quite subjective since it depends on visual observation. The formula evaluation between SDI and PCI shows that PCI described the actual field better than SDI. The result of Sensitivity Analysis in PCI Method conclude that the smaller the interval of segment unit, the greater the PCI value in condition the pavement distress is uneven in all segments. The dominant type of pavement distress in Lingkar Nagreg based on deduct values are ravelling and alligator cracking. It is also concluded that using Profilometer as a surveying instrument can be more effective and efficient since it produces various data in one time survey.